Electrical properties of silicon under nonuniform stress - Manku, T.; Nathan, A. (Journal of applied physics, 1993)
We present a detailed analysis of the electronic carrier transport in silicon when subject to a nonuniform stress distribution. Such a distribution gives rise to two independent current components which can be viewed in terms of carrier generation-recombination. One component arises as a result of the nonuniform stress induced position dependent density of states, and the other due to stress induced shifts in the band edges. The various parameters and coefficients describing these phenomena are presented.